Hopea sasidharanii (Dipterocarpaceae)—a new species from southern Western Ghats, India - Robi, Aloor Jose; Sujanapal, Puthiyapurayil; Sreekumar, Vadakkethil Balakrishnan; Sanil, Madambi Sankarankutty; Dantas, Kuttikkattu Jose (Phytotaxa, 2020)
A new species of the important timber trees family Dipterocarpaceae, Hopea sasidharanii Robi & Sujanapal, from Shenduruny Wildlife Sanctuary of Kerala, India is described and illustrated.